Introduction to hotel and resort management - Santos, Buen (Manila, Philippines C & E Publishing, 2010)
This book introduces the students to the departments that comprise hotels and resorts and how they interplay with each other to satisfy guest experience in their property .
Chapter1. Hotels and resorts overview -- Chapter2. The bare essentials -- Chapter3. Front office department -- Chapter4. Housekeeping department -- Chapter5. Food and beverages department -- Chapter6. Sales and marketing department -- Chapter7. Human resource and training department -- Chapter8. Finance department -- Chapter9. Security department -- Chapter10. Hotel casinos -- Chapter11. Travel agencies .
Includes bibliographical references.
Keywords: HOTEL MANAGEMENT; RESORT MANAGEMENT